2015
DOI: 10.1038/labinvest.2015.46
|View full text |Cite
|
Sign up to set email alerts
|

Triptolide abrogates growth of colon cancer and induces cell cycle arrest by inhibiting transcriptional activation of E2F

Abstract: Background Despite significant progress in diagnostics and therapeutics, over fifty thousand patients die from colorectal cancer annually. Hence there is urgent need for new lines of treatment. Triptolide, a natural compound isolated from the Chinese herb Tripterygium wilfordii, is effective against multiple cancers. We have synthesized a water soluble analog of triptolide, named Minnelide, which is currently in phase I trial against pancreatic cancer. The aims of the current study were to evaluate whether tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 27 publications
4
55
0
Order By: Relevance
“…33 Thus, inducing cancer cell apoptosis and inhibiting cancer cell proliferation are arguably the potent therapeutic methods for cancer treatment. [14][15][16][17][18] In this study, TPL significantly inhibited the proliferation of medulloblastoma Daoy cells and remarkably promoted Daoy cell apoptosis. [14][15][16][17][18] In this study, TPL significantly inhibited the proliferation of medulloblastoma Daoy cells and remarkably promoted Daoy cell apoptosis.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…33 Thus, inducing cancer cell apoptosis and inhibiting cancer cell proliferation are arguably the potent therapeutic methods for cancer treatment. [14][15][16][17][18] In this study, TPL significantly inhibited the proliferation of medulloblastoma Daoy cells and remarkably promoted Daoy cell apoptosis. [14][15][16][17][18] In this study, TPL significantly inhibited the proliferation of medulloblastoma Daoy cells and remarkably promoted Daoy cell apoptosis.…”
Section: Discussionmentioning
confidence: 50%
“…11,12 Triptolide (TPL) is the major active component extracted from the Chinese medicine herb Tripterygium wilfordii Hook F. 13 Reno et al 14 demonstrated that TPL inhibited the migration, invasion, and metastasis of lung cancer cells. Oliveira et al 16 proved that TPL abrogated the growth of colon cancer and induced cell cycle arrest by suppressing transcriptional activation of E2F. Oliveira et al 16 proved that TPL abrogated the growth of colon cancer and induced cell cycle arrest by suppressing transcriptional activation of E2F.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that TP inhibits cell growth and induces apoptosis in various cancers, primarily through multiple mechanisms, including the suppression of various signaling pathways and proliferative and antiapoptotic factors in a given cell type and under specific conditions. TP has been reported to strongly inhibit the transcription of numerous proinflammatory mediators [25]and was also implicated as a potent inhibitor of NF-kappa B and a promoter of transcriptional arrest [26][27][28][29][30]. Recent studies have shown that TP inhibits RNA polymerase-mediated transcription by targeting transcription factors, leading to the down-regulation of certain mRNA molecules [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, triptolide is also able to cause pancreatic cancer cell death through induction of apoptosis via inhibition of HSP70 [12]. Triptolide has also been demonstrated to abrogate cell growth of colon cancer and induce cell cycle arrest through inhibiting transcriptional activation of E2F [14]. A recent study also suggests that the induction of cell death by triptolide is modified by autophagy in cardiomyocytes [15].…”
Section: Introductionmentioning
confidence: 99%